Engineering Education Improvement Opportunities Using Computer Games - Jurāne, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This paper deals with differences between thinking styles of the new generation and previous one affected by information technologies in framework of engineering graphics education in Riga Technical University. This article deals with specific aspects of engineering graphics teaching and key principles of the educational computer games. Recommendations are offered for improvement of engineering graphics education and quality of teaching using computer games. Various models of games are offered according to intended learning objectives.